Polyamide engineering plastics : a comparative study of the effects of chemical structure and compounding additives on melt viscosity - Swanepoel, Elsa (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1994.